Cardiovascular Events After Primary Malignant and Non-Malignant Brain Tumour Diagnosis: A Population Matched Cohort Study in Wales (United Kingdom). (1st October 2022) - Poon, Michael T C; Jin, Kai; Brennan, Paul; Figueroa, Jonine; Sudlow, Cathie
Abstract: AIMS: It is uncertain whether the elevated cardiovascular diseases (CVD) risks in patients with brain tumours is due to differences in the distribution of risk factors. We compared CVD risks among patients with a primary brain tumour to a matched general population cohort. METHOD: Using data from the Secured Anonymised Information Linkage (SAIL) Databank in Wales, we identified adults aged ≥18 years with a diagnosis of brain tumour identified in the cancer registry between 2000-2014, and a matched cohort (case-to-control ratio 1:5) by age, sex and primary care provider from the general population. Outcomes included fatal and non-fatal major vascular events and venous thromboembolism (VTE). We used multivariable Cox models adjusted for clinical risk factors to compare risks. RESULTS: There were 2, 869 and 3, 931 people diagnosed with malignant and non-malignant brain tumours, respectively, in Wales. They were matched to 33, 785 controls. Within the first year of tumour diagnosis, malignant tumour was associated with VTE (hazard ratio [HR] 21.58, 95% confidence interval 16.12-28.88) and stroke (HR 3.32, 2.44-4.53). People with malignant tumour surviving one year had higher risks of VTE (HR 2.20, 1.52-3.18) and stroke (HR 1.45, 1.00-2.10) compared to their matched controls. Individuals with non-malignant tumours had higher risks of VTE (HR 3.72, 2.73-5.06), stroke (HR 4.06, 3.35-4.93) and aortic and peripheral arterial disease (HR 2.09, 1.26-3.48) within the first year of diagnosis compared with their controls. CONCLUSION: The elevated risks of CVD suggest risk reduction a potential strategy to improve life quality and survival in people with malignant and non-malignant brain tumour.